2021
DOI: 10.3389/fcimb.2021.682635
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Biophysical Properties of the Sorting Platform Pods in the Shigella Type III Secretion System

Abstract: Shigella flexneri, causative agent of bacillary dysentery (shigellosis), uses a type III secretion system (T3SS) as its primary virulence factor. The T3SS injectisome delivers effector proteins into host cells to promote entry and create an important intracellular niche. The injectisome’s cytoplasmic sorting platform (SP) is a critical assembly that contributes to substrate selection and energizing secretion. The SP consists of oligomeric Spa33 “pods” that associate with the basal body via MxiK and connect to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 52 publications
(132 reference statements)
4
16
2
Order By: Relevance
“…The D ~ 1.3 µm 2 /s diffusive state is consistent with our previous result obtained with PAmCherry-YeSctL, based on which we 10 concluded that both YeSctQ and YeSctL diffuse at the same slow rate as part of the same complex (18). The SctLQ interaction is also supported by a number of previous studies (17,19,20). On the other hand, the D ~ 3.1 µm 2 /s YeSctL diffusive state has not been previously observed.…”
Section: Yesctl Shares One Diffusive State With Yesctqsupporting
confidence: 92%
See 3 more Smart Citations
“…The D ~ 1.3 µm 2 /s diffusive state is consistent with our previous result obtained with PAmCherry-YeSctL, based on which we 10 concluded that both YeSctQ and YeSctL diffuse at the same slow rate as part of the same complex (18). The SctLQ interaction is also supported by a number of previous studies (17,19,20). On the other hand, the D ~ 3.1 µm 2 /s YeSctL diffusive state has not been previously observed.…”
Section: Yesctl Shares One Diffusive State With Yesctqsupporting
confidence: 92%
“…Subsequent work has focused on reconstituting such pod complexes in vitro . Se SctNLQ(19) and Sf SctLQK complexes(20) were successfully isolated, and the estimated size and shapes of these complexes were qualitatively consistent with cryo-ET pod densities. Based on these results, we speculate that the D ~ 1.3 μm 2 /s diffusive state we observe in wild-type cells and in Δ sctD mutants is likely not just a SctNLQ complex, but in fact a SctNLQK heterooligomer.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…6C). Overall, this result indicates that one molecule of SpaO per pod is able to simultaneously link the OrgA docking platform with the OrgB cradle suggesting a topological arrangement for the sorting platform pods (Fig 6D ), which differs from a previously proposed model 47 .…”
Section: Architecture Of the Core Sorting Platform Componentscontrasting
confidence: 63%